Little Mouse's painting - Wolkstein, Diane; Begin-Callanan, Maryjane (New York : Morrow Junior Books, 1992)
Little Mouse creates a painting which looks like three different things to her three friends, all of whom find themselves in it.
*SLJ*
*LJ*
4.4
K-3
Keywords: Artists -- Fiction; Mice -- Fiction; Animals -- Fiction; Artists -- Fiction; Mice -- Fiction; Animals -- Fiction